The ethics of the novel in the life of the town: provincial communities in the works of Fyodor Dostoevsky and George Eliot - Chadwick, P (2017)
This thesis analyses the function of the provincial town in the novels of Fyodor Dostoevsky (1821-1881) and George Eliot (1819-1880). It demonstrates that the small town, far from being a neutral backdrop to their narratives, functions as a sociological space in which to appropriate or challenge the discourses of modernity with which Dostoevsky and Eliot were explicitly preoccupied. The first chapter examines how their provincial communities negotiate biblical narrative in a world in which, thanks to nineteenth-century attempts to historicise the Bible, an acceptance of the Bible’s authoritative status is no longer a given. The instability of language itself is then interrogated in my second chapter, which shows that the transition from denotative, referential meaning to connotative, abstract forms causes ethical and narrative tension within the world of the novel, and which explores the aesthetics and ethics of gossip in the provincial town and novel. The third chapter details what becomes of the nineteenth-century discourse of heroism when characters seek to enact it in a provincial setting, showing that the environment of the provincial town proves hostile to heroic ambition, whilst the fourth argues that the provincial application of professional discourse (particularly that of medicine and the law) is critiqued and perfected by these authors. Through the analysis of this discourse, it is shown that Eliot and Dostoevsky’s treatment of provincialism is ambivalent. As urban intellectuals who did not consent to inhabit the provincial milieu they depict, they in many respects censure the world they describe. However, this censure is not absolute, and through their chosen setting, as well as their chosen genre of the novel, they provide ethical instruction for their readers, then and now. Ethics, for them, are best tested in community, and explored in narrative.